Secagem de polpa de graviola em spray-dryer e liofilizador: Avaliação das características físico-químicas, higroscópicas e morfológicas - Cavalcante, Carlos Eliardo Barros (2016)
This study aimed to obtain soursop pulp powder by two drying methods (spray-drying and freeze drying). Initially, we evaluated the influence of process conditions (inlet air temperature in the spray-drying process, drying time in the freeze drying process and concentration of maltodextrin as a drying aid in both cases) on yield, moisture and the hygroscopicity of these powders through experimental design. Pulps soursop powder obtained in both cases were characterized physico-chemical aspects, hygroscopic and morphological. The results indicated that for spray-drying process the best conditions are the use of 169 ° C as inlet air temperature and 17% maltodextrin, while for freeze drying process the best conditions were the use of 24% maltodextrin and a drying time of 24 h. Samples produced under these conditions had good physico-chemical aspects. The soursop pulp powder obtained in spray-drying process was characterized as being non-hygroscopic and too much caking formation, particles in spherical shape, varying sizes and smooth and uniform surface, in other hand the soursop pulp powder obtained in freeze drying process was characterized as non-hygroscopic and little caking formation, with particles without symmetry, disordered, without repetition of forms. Both powders presented adsorption isotherms type III (Format J), characteristic of foods with high sugar content, and the models that best set were the GAB for the powder obtained by spray-drying process and the OSWIN to that obtained by freeze drying process. Next, was assessed the stability of these powders stored in laminated packs under ambient conditions and it was found that storage under these conditions was effective in maintaining the quality of both the post for a period of 180 days.